Energy Potential and Utilization of Plantation Crops in Malaysia - K.O Lim; Zainal Alimudin Zainal Alaudin; Ghulam Abdul Quadir; Mohd, Zulkifly Abdullah (ASEAN Journal on Science and Technology for Development, 2000)
Energy Potential and Utilization of Plantation Crops in Malaysia